MODEL KLASTERISASI WILAYAH KOTA BERDASARKAN INDEKS INFRASTRUKTUR UNTUK PERENCANAAN STRUKTUR RUANG BERKELANJUTAN - Sabri Badruddin; Ashfa Achmad; Noer Fadhly (Prodi Magister Teknik Sipil Unsyiah, 2022)
Banda Aceh has nine sub-districts. These sub-districts have different levels of infrastructure growth. This will make it difficult for the government to make policies or decisions to determine a good strategy for developing sub-districts in Banda Aceh City. To make it easier to make a policy in terms of infrastructure development for the sub-district, it is necessary to cluster the area in Banda Aceh City. Regional clustering will group regions with the same level of development. This will make it easier for the government to make a decision. In this study, there were eight infrastructure indices, roads, electricity, water, solid waste, telecommunications, wastewater, drainage, and green open spaces (RTH). From the results of the study, it was found that the discussion of Banda Aceh City can be divided into 3 clusters. The first clustering is a cluster that does not have a prominent advantage over the eight variables but has the lowest variable level in the fields of roads, garbage, and wastewater. The sub-districts included in the first clustering are Kuta Alam District and Syiah Kuala District. The second clustering is clustering which has the highest variables in the field of drainage and roads but has the lowest variables in the fields of green open space and drinking water. The sub-districts included in the second clustering are Baiturrahman District, Banda Raya District, Jaya Baru District, Leung Bata District, and Ulee Kareng District. The third clustering is the cluster that has the highest variables in the field of solid waste, drinking water, wastewater, and green open space but has the lowest variable in the drainage sector. From the results of the Analytical Hierarchy Process (AHP), it is found that development priorities are road construction, green open space, electricity, drinking water, telecommunications, wastewater, drainage, and finally solid waste. The results of the SWOT analysis show that the graph is located in the strength and opportunity sections. So the policy taken for the future is the main focus on the construction of infrastructure for solid waste, wastewater, green open space, and telecommunications.